Autosomal recessive Parkinson’s disease and mitophagy - Plun-Favreau, Helene (Henry Stewart Talks, 2014)
Parkinson's disease (PD) and mitophagy, Pathogenic mutations in the genes associated with autosomal recessive PD interfere with the mitophagy pathway, Mitophagy is the selective degradation of damaged mitochondria by autophagy, Mitophagy allows optimal cellular energy production while it avoids toxic accumulation of damaged mitochondria in neurons.